2011
DOI: 10.1189/jlb.1210695
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the membrane insertion domain of proteinase 3, the Wegener's autoantigen, in RBL cells: implication for its pathogenic activity

Abstract: PR3, also called myeloblastin, is a neutrophil serine protease that promotes myeloid cell proliferation by cleaving the cyclin-dependent kinase inhibitor p21(cip1/waf1). In addition, it is the target of ANCA in GPA, a necrotizing vasculitis. Anti-PR3 ANCA binding to membrane-expressed PR3 triggers neutrophil activation, potentiating vascular inflammation. This study performed in RBL cells identifies the structural motifs of PR3 membrane anchorage and examines its impact on PR3 proinflammatory and proliferative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…In addition, unlike other neutrophil granule proteins, PR3 is coexternalized with phosphatidylserine (PS) during neutrophil apoptosis because of its association with phospholipid scramblase 1 and impaired macrophage phagocytosis (5). We recently reported that PR3, which is a peripheral membrane protein, has a hydrophobic patch essential for its membrane anchorage and for its proinflammatory activity (6). Accordingly, a hydrophobic patch-deficient PR3 mutant was not externalized on apoptosis and did not impair phagocytosis (6).…”
Section: G Ranulomatosis With Polyangiitis (Gpa) Formerly Calledmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, unlike other neutrophil granule proteins, PR3 is coexternalized with phosphatidylserine (PS) during neutrophil apoptosis because of its association with phospholipid scramblase 1 and impaired macrophage phagocytosis (5). We recently reported that PR3, which is a peripheral membrane protein, has a hydrophobic patch essential for its membrane anchorage and for its proinflammatory activity (6). Accordingly, a hydrophobic patch-deficient PR3 mutant was not externalized on apoptosis and did not impair phagocytosis (6).…”
Section: G Ranulomatosis With Polyangiitis (Gpa) Formerly Calledmentioning
confidence: 99%
“…We recently reported that PR3, which is a peripheral membrane protein, has a hydrophobic patch essential for its membrane anchorage and for its proinflammatory activity (6). Accordingly, a hydrophobic patch-deficient PR3 mutant was not externalized on apoptosis and did not impair phagocytosis (6).…”
Section: G Ranulomatosis With Polyangiitis (Gpa) Formerly Calledmentioning
confidence: 99%
See 3 more Smart Citations